Production and Characterization of Biodiesel from Allamanda Cathertica Oil - Evans, C. Egwim; Ibrahim, Z.A.; Onwuchekwa, Praise (Journal of Technology Innovations in Renewable Energy, 2013)
The gradual depletion of world petroleum reserves and the impact of environmental pollution due to increasing exhaust emissions have necessitated the urgent need to develop alternative energy resources, such as biodiesel fuel. Vegetable oil is a promising feedstock because it has several advantages; it is renewable and environmental friendly. The present study involves extraction of oil from Allamanda cathertica seed (Allamanda), Azadarachta indica and Jatropha caucus; conversion of the oil into biodiesel and the characterization of the methyl ester. Transesterification of the different feed stocks was conducted using sodium methaoxide (NaMt), sodium ethaoxide(NaEt), potassium methaoxide (PMt) and potassiumethaoxide (PEt) as catalysts, using a range of reaction temperatures (45, 50, 55, 60 and 65OC) and different rates of stirring. Result showed that Allamanda seed produced 54% oil yield using mechanical extraction. The biodiesel yield was 97% using NaMt and NaEt as catalysts, while azadarachta oil gave 95% yield with PEt catalyst alone. Jatropha oil gave a yield of 70% biodiesel with all the catalysts used. The yield of biodiesel from Allamanda oil with respect to temperature were 63, 88, 94, 46 and 20% respectively. Characterization of the biodiesel produced from Allamanda oil compared favorably with the ASTM standards, viscosity 5.4, flash point 115OC, refractive index 1.4756 and energy value 35.0MJ/L. The GCMS analysis of Allamanda methyl ester showed a range of 10 different methyl esters which includes hexadecanoic acid (24%), linoleic acid (14.8%), 13-Decosenoic acid (35.3%), 9-Octadecanoic acid (13.5%). The work concludes that allamanda oil could be a good and alternative feedstock to the edible feedstocks currently in use for biodiesel production.